Tuning the surface charges of MoO3 by adsorption of polyethylenimine to realize the electrophoretic deposition of high-exothermic Al/MoO3 nanoenergetic films. (5th November 2016) - Zhu, Yuhua; Li, Xueming; Zhang, Daixiong; Bao, Hebin; Shu, Yuanjie; Guo, Xiaogang; Yin, Yanjun
Abstract: Al/MoO3 nanoenergetic films (nEFs) were successfully prepared by the electrophoretic deposition (EPD) method. Polyethylenimine (PEI) was used to modify the surface charge of Al and MoO3 particles for the first time. In particular, the zeta potentials of Al/MoO3 were varied from negative value to highly positive one, which could contribute to the co-deposition of Al and MoO3 particles on the cathode. In addition, an effective adsorption of PEI on the particles was demonstrated by the FT-IR result. The kinetics of EPD process were investigated in this paper that the linear relationship of the equivalence ratio in the deposited film (Φd ) to that in suspension (Φs) was observed for Al/MoO3 nEFs. Furthermore, The FESEM, EDS and XRD analysis showed that Al/MoO3 nEFs were homogeneous mixed and composed of Al and MoO3 . The DSC and combustion processes results indicated that the exothermic behaviors were affected by the molar ratio of the fuel (Al) to the oxidizer (MoO3 ) in Al/MoO3 nEFs, and reached to the maximum of 3419 J/g and the most violent combustion as the Φs was 1.6, respectively. Al/MoO3 nEFs with excellent performance could lead to advances in the microelectro mechanical system technologies. Graphical abstract: The smooth and homogeneous Al/MoO3 nEFs were successfully prepared by electrophoretic deposition method and exhibited high heat release and best combustion performance. Highlights: Al/MoO3 nanoenergetic films were successfully prepared by electrophoretic deposition. The surface charge polarity of Al/MoO3 in isopropyl alcohol was changed by adding appropriate polyethylenimine. The maximum heat release was up to 3419 J/g by effectively adjusting kinetics of EPD process.